If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Xspuared + -6x = 27 Solving adeprsuX + -6x = 27 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6x' to each side of the equation. adeprsuX + -6x + 6x = 27 + 6x Combine like terms: -6x + 6x = 0 adeprsuX + 0 = 27 + 6x adeprsuX = 27 + 6x Divide each side by 'deprsuX'. a = 27d-1e-1p-1r-1s-1u-1X-1 + 6d-1e-1p-1r-1s-1u-1xX-1 Simplifying a = 27d-1e-1p-1r-1s-1u-1X-1 + 6d-1e-1p-1r-1s-1u-1xX-1
| 83/4+r=11/8 | | x-3=sqrt(4x)+9 | | 5[8-y]=30 | | 17=2p-3 | | x^3+y^3-xy+y^2=0 | | 4x+71=-33+8x | | 21+3t=9-3t | | 7b+2=13-b | | y(100-y)=2400 | | 5x(5+3x)= | | X*x*x*y=24 | | -10=4+7m | | X+(X+Y)=x | | 7x+8x+1=0 | | 8p-6=12 | | 27x=25 | | K^2+2=3k | | s(t)=-16t^2+144t+180 | | 3(2p+7)+8p(4p-9)= | | x(x+1)(5x+2)=0 | | 6k+10.5k=3K+12 | | K^2+2-3k=0 | | 7+49(2a+15)=-13 | | 2X+2y+z=72 | | 54=3x-30 | | 7+1(11)=P | | 7+1(X)=14 | | -11n-15n=8 | | -9(-5r-6+9m)= | | 7+1(2)=B | | -19=-0.5k | | 12-4x+9=0 |